2013
DOI: 10.1080/19320248.2013.786663
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Food Access in America: Considering the Role of Emergency Food Pantries in Areas without Supermarkets

Abstract: This study provides a more comprehensive depiction of the environment in which low-income households and other vulnerable populations acquire and purchase food by considering access to emergency food pantries in areas lacking supermarkets. The locations of food pantries were mapped against the map of supermarkets in 47 states and the District of Columbia to identify local areas without supermarkets and the percentage of these areas that have a pantry. Local area population characteristics were used to define s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 2 publications
1
11
0
Order By: Relevance
“…Results are consistent with other findings suggesting that, unlike for-profit retail services, food shelves are more likely to locate in areas with high levels of poverty and a known need for emergency food. 37,51 Our study additionally found that these areas include a high proportion of minority and immigrant/refugee residents. In this cross sectional study, our results might be interpreted to suggest that food insecure families make choices about where to live based on access to emergency food suppliers, but given the known choice constraints on housing among the poor, 52 this explanation is unlikely.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Results are consistent with other findings suggesting that, unlike for-profit retail services, food shelves are more likely to locate in areas with high levels of poverty and a known need for emergency food. 37,51 Our study additionally found that these areas include a high proportion of minority and immigrant/refugee residents. In this cross sectional study, our results might be interpreted to suggest that food insecure families make choices about where to live based on access to emergency food suppliers, but given the known choice constraints on housing among the poor, 52 this explanation is unlikely.…”
Section: Discussionsupporting
confidence: 58%
“…36 One recent nation-wide geographic analysis found that over 40% of census tracts without a supermarket in high-poverty areas had a food pantry supplying emergency food to area residents. 37 In this study, areas with a greater percentage of non-white residents and households receiving Supplemental Nutrition Assistance Program (SNAP) benefits were the most likely areas to have a food pantry, but not have access to a supermarket. This supports the notion that food pantries are likely a common and accessible source of food among these segments of the population.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Raising communication awareness towards food insecurity [33,56,60] Raising communication awareness towards food safety [29,56,60] Raising communication awareness towards waste [29,34,43] Solution to food poverty [34] Solution to excessive food production [34] Food waste prevention [29,34,43] Answers were rated on a 6-point Likert scale, with 1 representing the lowest score (total disagreement, lower extent, etc.) and 6 the highest (complete agreement, maximum extent, etc.).…”
Section: A Economicmentioning
confidence: 99%
“…Globally there is quite an extensive amount of literature on FRAs in various regions or countries, such as Australia [41,42], Austria [43][44][45][46], Canada [47,48], Belgium [49], Europe [12] Germany [50], Spain [51][52][53], Nordic Region [54], UK [55][56][57][58], and the US [25,59,60]. Some studies on food donations have been conducted also in Italy.…”
Section: Introductionmentioning
confidence: 99%